Hesperidin as a preventive resistance agent in MCF–7 breast cancer cells line resistance to doxorubicin - Rifki Febriansah; Dewi P.P. Dyaningtyas; Sarmoko; Nunuk Aries Nurulita; Edy Meiyanto; Agung Endro Nugroho (Asian Pacific Journal of Tropical Biomedicine, 2014)
Objective: To evaluate of hesperidin to overcome resistance of doxorubicin in MCF-7 resistant doxorubicin cells (MCF-7/Dox) in cytotoxicity apoptosis and P-glycoprotein (Pgp) expression in combination with doxorubicin. Methods: The cytotoxic properties, 50% inhibition concentration (IC50) and its combination with doxorubicin in MCF-7 cell lines resistant to doxorubicin (MCF-7/Dox) cells were determined using MTT assay. Apoptosis induction was examined by double staining assay using ethidium bromide-acridine orange. Immunocytochemistry assay was performed to determine the level and localization of Pgp. Results: Single treatment of hesperidin showed cytotoxic activity on MCF-7/Dox cells with IC50 value of 11 μmol/L. Thus, combination treatment from hesperidin and doxorubicin showed addictive and antagonist effect (CI>1.0). Hesperidin did not increase the apoptotic induction, but decreased the Pgp expressions level when combined with doxorubicin in low concentration. Conclusions: Hesperidin has cytotoxic effect on MCF-7/Dox cells with IC50 of 11 μmol/L. Hesperidin did not increased the apoptotic induction combined with doxorubicin. Co-chemotherapy application of doxorubicin and hesperidin on MCF-7/Dox cells showed synergism effect through inhibition of Pgp expression.